CRITICAL SUCCESS FACTORS OF SUPER TAX DEDUCTION INCENTIVES FOR R&D ACTIVITIES CARRIED OUT BY THE INDUSTRIAL SECTOR - Nurlaeli, Isna; Rahayu, Ning (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
In order to achieve Indonesia Gold 2045, with one of the missions being an advanced economy country, Indonesia needs to increase its Gross Domestic Product (GDP). One of the programs is to improve the quality of human resources and science and technology, which is carried out through increasing research and development activities. After further review, it turns out that spending on research and development activities compared to Indonesia's Gross Domestic Product is still low, private participation in research and development is still less than the government. The government makes a policy of providing super tax deductions to companies that carry out certain research and development activities in Indonesia. This research was conducted to determine the critical success factors (CSF) or success factors that must be considered by policy makers in implementing super tax deduction for research and development activities, which were carried out with a post positivist approach and data collection by in-depth interviews. Critical Success Factors (CSF) analyzed are divided into 3 dimensions, namely relevance, effectiveness, and efficiency. In the dimension of relevance, the form of super tax deduction incentives is the right form if the cost factor constraint in hindering research and development activities carried out by the industry applies ceteris paribus, and it is necessary to adjust the form of incentives according to industry needs. In addition, it is necessary to determine clear overall policy targets with the preparation of performance indicators. The dimension of effectiveness shows that in implementing the policy, it is necessary to conduct an evaluation to find out the cause of the company's low enthusiasm in conducting research and development activities and proposing incentives, and it is necessary to increase the intensity of socialization and adequate coordination between the ministries/agencies involved. In terms of efficiency, the use of the Online Single Submission (OSS) system in the implementation of incentive submissions needs to be optimized by developing a synchronized OSS system and supporting transparency in policy implementation.